Embedded Based Priority Traffic Controller for Ambulance and Fire Brigade - Jasmin, M.; Philomina, S.; Virgin, G. Angelo (International Journal of Psychosocial Rehabilitation, 2018)
In emergency system, the transfer of patients to the hospital should be in fast and save manner to increase the rescue and survival rates. Thus, the ambulances take the short and safe way to the emergency department at a hospital. To satisfy this, this paper tackles the problem of road jamming by controlling the underlying traffic lights and selecting the optimal path depending on crowed sensor readings.